EVIDENCE FOR THE EARLY DIFFERENTIATION OF THE CORE FROM PT-RE-OS ISOTOPE SYSTEMATICS OF 2.8-GA KOMATIITES - Puchtel I.S.; Humayun M.; Walker R.J.; Brandon A.D. (My University, 2005)
Komatiite samples from the 2.8-Ga Kostomuksha greenstone belt in the Baltic Shield define Pt–Os and Re–Os isochrons with ages of 2816 ± 190 and 2880 ± 83 Ma, respectively. The mean initial 186Os / 188Os and 187Os / 188Os ratios calculated at T = 2821 Ma are 0.1198341 ± 7 and 0.11042 ± 69 (γ187Os = + 2.5 ± 0.6), respectively. This Os isotopic composition characterizes that of the source of the Kostomuksha komatiite and is 53 ± 6 ppm and 2.5 ± 0.6% more radiogenic in 186Os/188Os and 187Os/188Os, respectively, than the putative contemporary convecting mantle. The coupled 186Os–187Os enrichment cannot be the result of incorporation of the material of aged recycled oceanic crust into the source of the plume, as five to six times more crustal component is required to create the 186Os-enrichment than the 187Os-enrichment observed. Moreover, the radiogenic 186Os / 188Os ratio combined with the subchondritic Pt/Os in this source calculated from the HSE abundance data is inconsistent with any model of Os isotopic evolution that involves crustal recycling, as these models require substantially suprachondritic Pt/Os in the hybrid sources. The coupled 186Os–187Os enrichment in the source of the Kostomuksha komatiite is best explained via derivation of most of the Os from the outer core. This is most consistent with the Kostomuksha komatiites originating from a mantle plume that arose from the core–mantle boundary (CMB). If this interpretation is correct, the data provide minimum constraints on the 186Os / 188Os and 187Os / 188Os ratios of the outer core at 2.8 Ga. The existing models of core crystallization based on experimentally determined solid metal–liquid metal partition coefficients for Pt, Re, and Os can adequately explain the Os isotopic composition of the Kostomuksha mantle source, although require the onset of inner core crystallization several hundred million years prior to formation of the Kostomuksha plume. Based on thermodynamic models, such an early onset of inner core crystallization would require a relatively low heat flux across the CMB of ∼3 TW and the presence of > 100 ppm K in the core. The results of this study combined with the HSE abundance data for the source of komatiites at Kostomuksha indicate that core–mantle interaction, at least in this instance, could occur in the form of isotopic exchange without significant mass transfer from the core to the mantle.
Keywords: Archaen komatiite; Pt–Re–Os isotope sytematics; highly siderophile elements; core–mantle interaction; Докембрий::Архей; Precambrian::Archean